Bilateral Pulmonary Aspergilloma Caused by an Atypical Isolate of Aspergillus terreus - Khan, Z. U. (American Society for Microbiology, 2000)
A case of bilateral pulmonary aspergilloma caused by an atypical isolate of Aspergillus terreus is described. The diagnosis was established by the presence of septate, dichotomously branched fungal elements in freshly collected bronchoalveolar lavage and sputum specimens and by repeated isolation of the fungus in culture. Specific precipitating antibodies against the A. terreus isolate were demonstrated in the patient's serum. The isolate was atypical as it failed to produce fruiting structures on routine mycological media, but it did so on extended incubation on potato flake agar and produced globose, relatively heavy-walled, hyaline accessory conidia (formerly termed aleurioconidia) on both vegetative and aerial mycelia. Also, it produced an intense yellow diffusing pigment in the medium. The report underscores the increasing importance of A. terreus in the etiology of pulmonary aspergillosis. It is suggested that A. terreus antigen be included in the battery of serodiagnostic reagents to facilitate the early diagnosis of infections caused by this species.